Empowerment Program of Disabled Students through Fashion Design and Practical Culinary Skills Training at SLBN 1 Pembina Makassar - Nurul Anggraeni; Rezkia Yusuf; Nurul Musfira; Muh. Putra Satri Mu’min; Andi Eka Putri Octarima Abriadie (Jurnal Pengabdian Masyarakat Bestari, 2023)
This empowerment program aims to train and develop the creativity and skills of special needs students in the fields of fashion and culinary. In this activity, the method used was participatory training with several stages, including the stage of material presentation (introduction to tools and materials and introduction to work safety), then allowing students to practice accompanied by the training supervisor. Then, the data collection methods used are observation and interviews. The results of the study showed that the skills, self-confidence, and independence of special needs students were increasing, as evidenced by the competitions that they participated in and that reached the National Office. Then, some alumni have businesses in the fashion and culinary sectors.